ESTIMASI KEDALAMAN BATUAN DASAR DI DESA KAMPUNG MANGGIS KECAMATAN PADANG PANJANG BARAT MENGGUNAKAN METODE INVERSI ROBUST 2D DATA GEOLISTRIK TAHANAN JENIS KONFIGURASI WENNER - Basra Kurniawan (PILLAR OF PHYSICS, 2014)
The aimed of this research are to determine the resistivity and the depth of basement rocks in Kampung Manggis Padang Panjang Barat area. The resistivity and the depth of basement rocks in Kampung Manggis are important to know to anticipate landslide caused excessive load on the surface of the earth. This research use resistivity geoelectrical method with Wenner configuration. The data of this research were taken  four tracks using ARES (Automatic Resistivity). The data were processed using Res2Dinv v3,59 software with Robust 2D inversion to obtain a 2D cross-section beneath the earth’s surface. The result of this research showed that type of basement rock in Kampung Manggis Padang Panjang Barat is an igneous rock groups, namely Andesite. The resistivity of this Andesite is 170 – 790 Ωm. The depth of basement rocks below the earth’s surface varies, which generally more than 20 m deepness around Kampung Manggis Padang Panjang Barat area . Keywords – Basement Rocks, resistivity, Wenner, Robust 2D inversion